Strengthening women's tenure rights and participation in community forestry in central Uganda - Mukasa, C.M.; Tibazalika, A.; Banana, A.Y.; Mwangi, E.; Mutimukuru-Maravanyika, T. (Routledge, 2021)
Although women’s rights and participation in forestry are recognized and addressed in Uganda policy and law, the actual practice on the ground still excludes women from participating in decision making and benefiting from forest and tree resources. Cultural norms, beliefs and practices constrain women’s access and control of forest and tree resources. This undermines their investments in sustainable forest use and management and further limits their participation in decision making and benefit sharing. This research explored ways in which women’s rights and access to forests could be strengthened, and mechanisms for enhancing their participation in forest resource management, decision making and benefits sharing. We present lessons from and outcomes of processes of facilitation and negotiation using an adaptive collaborative management (ACM) approach in six randomly selected communities in four districts in Central Uganda. After six years of implementing ACM activities, our findings suggest that despite being usually regarded as “sticky,” with careful facilitation and negotiation, change of gender-based customary norms can be speeded up. These processes can also help determine more just directions of cultural change thereby offering potential for enhancing gender equity over a short period of time. We have learnt that the involvement of men, the provision of safe platforms for women to express themselves, exposure through exchange programmes, leadership training (for both men and women) and support from collaborating partners are essential for enabling gender-transformative outcomes.